STRATEGI MOCHAMMAD RAMLIE DALAM PEMILU LEGISLATIF KOTA TANGERANG SELATAN TAHUN 2019 - Monica Ayu Dhamayanti (2023)
This research examines the political campaign strategy used by Moch Ramlie in the 2019 South Tangerang City Legislative Election. The electoral system for the 2019 legislative elections in South Tangerang City uses a proportional election system with a fixed list of candidates (DCT). Using this system, voters give their voting rights to political parties and seats in the DPRD are distributed based on the number of votes received by each political party. The phenomenon of the South Tangerang Golkar party in maintaining and increasing the number of seats in the DPRD cannot be separated from the influence of a elite political figure named Moch Ramlie. He is the Chairperson of the South Tangerang City DPRD for the 2014-2019 period who again advanced in the legislative elections in 2019. This study uses a qualitative approach and the type of research used is descriptive qualitative research. The theory used is the theory of political strategy and political marketing. Primary data in this study were obtained by conducting interviews with informants and secondary data derived from books, journals and previous research. The results showed that the election of Moch Ramlie in the 2019 South Tangerang City Legislative Election using three approaches to capital, namely political capital, social capital, and economic capital, was considered successful. In addition to the strength of political parties, Moch Ramlie's popularity and personality are the main factors in winning voters' votes. In the popularity factor, the researcher identified the existence of Betawi ethnic identity politics which also helped Moch Ramlie in winning the 2019 South Tangerang City Legislative Election. However, it is important to note that Betawi ethnic identity politics must be carried out in a spirit of inclusiveness and non-discrimination against other groups. Keywords: Marketing Politics, Legislative Elections, Political Campaign Strategy